Phenological responses to extreme droughts in a Mediterranean forest - Misson, Laurent; DEGUELDRE, DAVID; COLLIN, CHRISTIAN; RODRIGUEZ, RAQUEL; ROCHETEAU, ALAIN; OURCIVAL, JEAN-MARC; Rambal, Serge (Global Change Biology, 2011)
Mediterranean regions are projected to experience more frequent, prolonged and severe drought as a consequence of climate change. We used a retractable rainfall shelter, to investigate the impact of extreme droughts on the development of Quercus ilex leaves, flowers and fruit. In 2008, 97% of rainfall was excluded from a forest plot during the autumn, representing 50% of the 1127 mm of rain that fell during the year. In 2009, 87% of rainfall was excluded during the spring, representing 58% of the 749 mm that fell during the year. The rainfall shelter did not impact neither incident radiation nor air temperature. Autumn rainfall exclusion did not significantly affect leaf, flowers or fruit development. Spring rainfall exclusion resulted in larger and more sustained depression of leaf water potential during the key phases of foliar and floral development. Consequently, only half of the sampled trees (6) reached the shoot lengthening stage which leads to functionally mature leaves (phenophase 4), with one abandoning leaf development at budburst (phenophase 3) and the other two at the bud swelling stage (phenophase 2). All trees of the control plot passed phenophase 4, with most reaching complete leaf development. The impact of extreme droughts on flower development differed between the sexes. The spring exclusion had no effect on male flower, but only one of six trees completed female fruit maturation, compared with four in the control plot. The difference between the male and female drought impacts is likely attributable to the occurrence of male floral development before the period of lowest leaf water potential, and to the lower resource allocation requirements of male flowers. The information provided by our experimental approach may constitute a crucial step to evaluate the impact of increasing drought due to climate change on the most dominant Mediterranean tree species and to help drawing a full picture of the ecological consequences of the decline in water resource on forest dynamics under changing conditions.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate changes; Extreme events; flowering; fruiting; leaf-unfolding; rainfall changes